+971 голосов
2.6 млн просмотров

1. Упростите выражение (7а + 2ь) –(3а - b) (4а + 5b).​

назад от 1 1 1 в категории Алгебра

2 Ответы

+125 голосов

Ответ: 7а+ 2b -12a^2 -11ab +5b^2

Объяснение:

(7а + 2b) –(3а - b) (4а + 5b)=  7а +2b - ( 12a^2+15ab - 4ab - 5b^2)=

= 7a+2b-12a^2-15ab +4ab+ 5b^2 = 7а+ 2b -12a^2 -11ab +5b^2

назад от Начинающий (324 баллов)
+142 голосов

Ответ:

(7а + 2ь) –(3а - b) (4а + 5b)

7а+2b-(12a^2+15ab-14ab-5b^2)

7a+2b-(12a^2+11ab-5b^2)

7a+2b-12a^2-11ab+5b^2

назад от (16 баллов) 1 2 2
...